Identification of amino acids in the transmembrane and juxtamembrane domains of the platelet-derived growth factor receptor required for productive interaction with the bovine papillomavirus E5 protein. - Petti, L M (1997)
The bovine papillomavirus E5 protein forms a stable complex with the cellular platelet-derived growth factor (PDGF) beta receptor, resulting in receptor activation and cell transformation. Amino acids in both the putative transmembrane domain and extracytoplasmic carboxyl-terminal domain of the E5 protein appear important for PDGF receptor binding and activation. Previous analysis indicated that the transmembrane domain of the receptor was also required for complex formation and receptor activation. Here we analyzed receptor chimeras and point mutants to identify specific amino acids in the PDGF beta receptor required for productive interaction with the E5 protein. These receptor mutants were analyzed in murine Ba/F3 cells, which do not express endogenous receptor. Our results confirmed the importance of the transmembrane domain of the receptor for complex formation, receptor tyrosine phosphorylation, and mitogenic signaling in response to the E5 protein and established that the threonine residue in this domain is required for these activities. In addition, a positive charge in the extracellular juxtamembrane domain of the receptor was required for E5 interaction and signaling, whereas replacement of the wild-type lysine with either a neutral or acidic amino acid inhibited E5-induced receptor activation and transformation. All of the receptor mutants defective for activation by the E5 protein responded to acute treatment with PDGF and to stable expression of v-Sis, a form of PDGF. The required juxtamembrane lysine and transmembrane threonine are predicted to align precisely on the same face of an alpha helix packed in a left-handed coiled-coil geometry. These results establish that the E5 protein and v-Sis recognize distinct binding sites on the PDGF beta receptor and further clarify the nature of the interaction between the viral transforming protein and its cellular target.